2020
DOI: 10.3389/fnhum.2020.591671
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stochastic Galvanic Vestibular Stimulation on Body Sway and Muscle Activity

Abstract: Objective: This study aimed to investigate whether galvanic vestibular stimulation with stochastic noise (nGVS) modulates the body sway and muscle activity of the lower limbs, depending on visual and somatosensory information from the foot using rubber-foam.Methods: Seventeen healthy young adults participated in the study. Each subject maintained an upright standing position on a force plate with/without rubber-foam, with their eyes open/closed, to measure the position of their foot center of pressure. Thirty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 37 publications
1
26
1
Order By: Relevance
“…A previous study reported that nGVS at 0.2 mA decreased body sway in patients with vestibular disorder, while that at 0.5 mA increased body sway (20). Another previous study similarly reported that nGVS at 1 mA increased the COP-TL in a healthy young population (19). Therefore, our finding that nGVS at 0.6 mA increases COP-TL is consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A previous study reported that nGVS at 0.2 mA decreased body sway in patients with vestibular disorder, while that at 0.5 mA increased body sway (20). Another previous study similarly reported that nGVS at 1 mA increased the COP-TL in a healthy young population (19). Therefore, our finding that nGVS at 0.6 mA increases COP-TL is consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…A possible mechanism for this alteration is interference by nGVS in vestibular information carried by the irregular vestibular neurons originating from Type I Hair Cells ( 16 ). Although nGVS is thought to alter the degree of vestibulospinal reflexes and body sway in both patients with vestibular disease ( 17 ) and healthy participants ( 18 , 19 ), it remains unclear whether nGVS alters the VOR. In the present study, therefore, we investigated whether nGVS induces changes in VOR-gain.…”
Section: Introductionmentioning
confidence: 99%
“…A square-wave pulse GVS of 3 mA for 200 ms with an electrode over the bilateral mastoid process, similar to that in this study, did not induce pain ( Matsugi et al, 2017 ; Okada et al, 2018 ), and continuous direct current GVS of 1 mA induced a slight sensation in about 25% of young adult participants ( Nakamura et al, 2020 ). On the contrary, nGVS of 1 mA intensity using the same stimulator as in our study did not induce pain in 30 young adults in a static prone position ( Matsugi et al, 2020a ) and 17 young adults in a static standing position ( Matsugi et al, 2020b ). Therefore, an intensity of 0.4 mA for nGVS might be below the threshold of sensation, and based on these findings, we believe that nGVS at 0.4 mA cannot induce pain in the elderly population.…”
Section: Discussioncontrasting
confidence: 48%
“…In the vestibular system, a particular level of mechanical noise on the semicircular canals can improve the performance of the vestibular system in peripheral sensory processing ( Flores et al, 2016 ). nGVS-induced modulation of the threshold of the vestibulospinal response ( Matsugi et al, 2020a ) is thought to contribute to body sway changes ( Matsugi et al, 2020b ; Sprenger et al, 2020 ). The vestibular system contributes to autonomic regulation ( Yates et al, 2014 ; McCall et al, 2017 ); therefore, nGVS might modulate AP and HR variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation